The Differences in Blood Lead Levels in Women with Gestational Hypertension or Pre-Eclampsia and Women with Normal Pregnancy (A Study in the North Coast of Java, Brebes District) - Suhartono Suhartono; Apoina Kartini; Budiyono Budiyono; Yusniar Hanani Darundiati (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Gestational Hypertension (GH) and Pre-eclampsia (PE) are the leading causes of maternal death. Exposure to lead from the environment, especially agricultural activities, may cause pregnant women to suffer from GH and PE. GH/ PE may occur through oxidative stress mechanisms and progressive endothelial damage. Brebes District is one of the areas with the highest Maternal Mortality Rate (MMR) in Central Java where the occurrence of GH/PE was a lot. This study aimed to analyze the differences in Blood Lead Levels (BLL) in pregnant women with GH/PE and normal pregnant women in Brebes District. Methods: This study used a cross-sectional design. By selecting and applying inclusion criteria, 18 subjects were selected for the GH/PE group (case group), and 46 subjects were selected for the normotension group (control group). Measurement of BLL was carried out using the Atomic-Absorption Spectrometry (AAS). Some of the statistical methods used were independent t-test, Mann-Whitney test, Chi-square test, multivariate logistic regression test, and Rank-Spearman correlation test. The risk estimate was calculated from the Odds-Ratio (OR) and 95% Confidence Interval (CI). Results and Discussion: The median value and range of the BLL in the case and control groups were 40.20 g/dL (15.50-89.20) and 32.75 g/dL (3.60-42.80), respectively (p = 0.011). Pregnant women with the BLL of â‰¥ 35.15 g/dL had eight times the risk of experiencing GH/PE (Adj-OR = 8.1; 95% CI = 1.7-39.0). Exposure to lead will increase the production of Reactive Oxygen Species (ROS), resulting in oxidative stress and endothelial dysfunction in addition to increasing the blood pressure. Conclusion: The BLL in pregnant women with GH/PE is higher than women with normal pregnancy, and the BLL in the high category is a risk factor for GH/PE.